Chile : 2010 Article IV Consultation-Staff Report; Staff Supplement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Chile. (IMF Staff Country Reports; Country Report ;, 2010)
Chile's economy has withstood successfully two consecutive large negative shocks-the global financial crisis and the February 2010 earthquake. The financial system has weathered the crisis well and the cyclical deterioration of credit quality has been moderate. Large-scale private and public reconstruction spending should continue to boost growth. The authorities' intentions to enhance the supervision of the financial sector, including the planned move toward consolidated supervision of financial conglomerates, are encouraged. The prudential framework is strengthened by adopting a functional approach to regulation and supervision.